Traditional ecological institutions and natural resource governance – a study of selected traditional communities in Ghana - Blankson, Edwin Kodwo Kuntu (Technium Social Sciences Journal, 2021)
Studies on Natural Resource Governance (NRG) have often explored the institutions, principles and processes of governance and promoted the practice of endogenous governance systems as a better alternative to statutory imported governance systems. Empirical studies on Natural Resource Governance (NRG) in traditional communities have however not explored sufficiently the dynamics and processes of integrating Traditional Ecological Institutions (TEIs) in to NRG. The main objective of the study was to explore the nature of resource governance in Boabeng – Fiema, Tafi – Atome and Amansuri communities in Ghana. Additionally, the study examined the role of Traditional Ecological Institutions in the governance process and explained the role played by the TEIs in achieving the governance principles. The study employed a multiple-case study approach using a qualitative study design. A combination of convenience and purposive sampling were used to select the respondents. Data collection was through interviewing, focus group discussion, and observation. Qualitative data analysis involved thematic analysis, discourse analysis, and interpretative phenomenological analysis. The study revealed that the governance system relied mostly on traditional ecological institutions, laws, processes. Moreover, the key institutions that were major governance players were the chieftaincy, the traditional priesthood, and the clan/ family institutions. The roles played by the institutions differed from community to community but mainly centered on law enforcement, monitoring, and review of ecological laws on natural resource use and conservation. The main recommendation was that, for the integration of TEIs into NRG system to be improved, there was the need to properly document the TEK and Traditional Governance regimes that justified the involvement of these institutions in NRG